2019
DOI: 10.47536/jcrm.v20i1.235
|View full text |Cite
|
Sign up to set email alerts
|

Participatory science and directed survey methods: A case study with odontocetes in the Maui Nui region of the Hawaiian Islands

Abstract: Given the difficulties and costs often associated with surveying cetaceans, enlisting members of the public to collect data offers a promisingalternative approach. Comparison of cetacean ‘participatory science’ (also known as ‘citizen science’) data with data collected during traditionalscientific studies helps reveal the strengths and weaknesses of a participatory science approach. With a large number of vessel operators on thewater throughout the year, including dolphin-oriented tour boats, the Hawaiian Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…A mirror of this diel pattern was observed at the coastal EAR sites of this study, with more acoustic activity during the daytime hours, coinciding with spinner dolphin resting behavior, and little or no signaling at night. This strong diurnal bias supports the conclusion that the majority of acoustic signals recorded in this study was most likely produced by spinner dolphins, which associate with coastal waters more than any of the other species present in the region (Howe et al, 2019). However, a limited contribution of signals from bottlenose and/or spotted dolphins cannot be ruled out.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…A mirror of this diel pattern was observed at the coastal EAR sites of this study, with more acoustic activity during the daytime hours, coinciding with spinner dolphin resting behavior, and little or no signaling at night. This strong diurnal bias supports the conclusion that the majority of acoustic signals recorded in this study was most likely produced by spinner dolphins, which associate with coastal waters more than any of the other species present in the region (Howe et al, 2019). However, a limited contribution of signals from bottlenose and/or spotted dolphins cannot be ruled out.…”
Section: Discussionsupporting
confidence: 85%
“…One major assumption of this study is that the significant majority of acoustic signals identified are spinner dolphin signals. Previous passive acoustic monitoring, vessel-based survey efforts, and sightings reported through a participatory science program in Maui Nui identified the following odontocetes in the region: melon-headed whales (Peponocephala electra), short-finned pilot whales (Globicephala macrorhynchus), false killer whales (Pseudorca crassidens), pantropical spotted dolphins (Stenella attenuata), and bottlenose dolphins (Howe et al, 2019;Howe and Lammers, 2021). Melon-headed whales were a rare occurrence in Maui Nui and would be unlikely to have a significant acoustic presence in the recordings of this study (Howe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations